Experimental Investigation on the Effects of DBD Plasma on the Film Cooling Effectiveness of a 30-Degree Slot - Kim, Ye Jee; Kim, Gi Mun; Shin, Youhwan; Kwak, Jae Su (MDPI AG, 2017)
The effects of dielectric barrier discharge (DBD) plasma on the film cooling effectiveness of a 30-degree slot was experimentally investigated in a low-speed wind tunnel. The pressure sensitive paint (PSP) technique was used to measure the film cooling effectiveness, and two blowing ratios (0.5 and 1.0) were tested. A sinusoidal waveform with a 1-kHz frequency was supplied to the exposed electrode. Two input voltages (6 and 7 kV) and two exposed electrode locations were considered. The results showed that the film cooling effectiveness of the slot was higher for the blowing ratio of the 1.0 case than that for the blowing ratio of the 0.5 case regardless of plasma operation. The higher input voltage case (7 kV) showed higher film cooling effectiveness than the lower input voltage case (6 kV). The improvement in film cooling effectiveness facilitated by the DBD plasma was more significant when the coolant had less momentum. The maximum improvement of the area averaged film cooling effectiveness was 2.3% for the case with the exposed electrode located at the slot exit and a blowing ratio of 0.5.
Keywords: DIELECTRIC BARRIER DISCHARGE; FLOW-CONTROL; ACTUATORS; OPTIMIZATION; UNCERTAINTY; MECHANISMS; RESPONSES; PRESSURE; AIR